Nitrogen ligands: The transition metal catalyzed reaction of aryl halides with olefins (Mizoroki-Heck), phenylboronic acid (Suzuki coupling) and Buchwald-Hartwig amination, new catalysts and effect of co-catalysts - Aryl halide activation - Part I - Iyer, S; Kulkarni, GM; Ramesh, C; Sattar, AK (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2005)
Nitrogen ligands are an excellent alternative for the traditional P-ligands in the Pd catalyzed Mizoroki-Fleck reaction, Suzuki coupling and Buchwald-Hartwig aryl amination. Pd complexes of dimethyl glyoxime, 8-hydroxyquinoline, salen, picolinic acid, and DAB ligands gave high yields of the E-cinnamates and E-stilbenes from aryl iodides. Acetophenone oxime N, N-dimethybenzylamine and ferrocenyl oxime palladacycle are better catalysts with comparable yields, high TON (95, 000) and TOF's (2, 500 h(-1)) to P-ligand catalysts. Aryl bromides and in a few cases, aryl chlorides could also be activated by these complexes by the use of Lewis acid and (C(4)H(9))(4)NI as additives. Cy-DAB ligands gave good yields with electron rich aryl bromides and the use of ionic liquid improve the yield. These N-ligand metal complexes can be readily synthesized and the ligands possess the advantage of easy functional group modifications and convenient synthetic methods compared to P-ligands. The degradation reactions associated with P-ligands are not observed in the N-ligands, with comparable, high thermal, moisture and air stability and insensitivity. Activation of aryl bromides (Mizoroki-Fleck reaction, Suzuki reaction) could be achieved in high yields, TON and TOF (86-94% yield, TON: 36, 000-90, 000, TOF:6, 000-11, 500 h-1) catalyzed by monomeric amine and oxime palladacycles (Cat-8, 11, 13 B) with a N-heterocyclic carbene ligand better than a phosphorous ligand. Molten (C(4)H(9))(4)NBr is an efficient ionic liquid medium for the Mizoroki-Fleck reaction of aryl bromides, giving higher yields. Low to moderate yields of aryl amination are obtained with the carbene pallaclacycle and N, N-dibenzyl piperazine Pd complexes.
Keywords: DAB; DMG; Mizoroki-Heck reaction; nitrogen ligands; Palladacycle